Rentabilidad de cooperativas multiactivas de Barranquilla. Análisis empírico desde la información contable (2019)
Multiactive cooperatives in the city of Barranquilla have been a significant contribution to the local economy, the region and the country for many years. Their economic performance is remarkable, even though they are in an increasingly harsh and demanding economic system. Various factors such as competitiveness, productivity and profitability play important roles in the development of the economic activity of any company, and more in this type of solidarity sector companies that have different economic activities to develop. Profitability is one of the variables with the greatest impact, and this variable will be discussed in this research work; where, through the study of the accounting information reported in 2017 to the Superintendencia de la Economía Solidaria de Colombia,, an entity that monitors these types of companies; the main sectors in which they carry out their economic activity may also be characterised by financial statements which they have issued; and through the statistical model Pearson, which seeks linear correlation, will be identified the incidence that has the Profitability the size of